Reconfigurable weblabs based on the IEEE1451 Std - Costa, Ricardo J. (2014)
Technology plays a double role in Education: it can act as a facilitator in the teaching/learning process and it can be the very subject of that process in Science & Engineering courses. This is especially true when students perform laboratory activities where they interact with equipment and objects under experimentation. In this context, technology can also play a facilitator role if it allows students to perform experiments in a remote fashion, through the Internet, in a so-called weblab or remote laboratory. No doubt, the Internet has been revolutionizing the educational process in many aspects, and it can be stated that remote laboratories are just an angle of that on-going revolution. As any other educational tool or resource, the i) pedagogical approach and the ii) technology used in the development of a remote laboratory can dictate its general success or its ephemeral existence. By pedagogical approach we consider the way remote experiments address the process by which students acquire experimental skills and link experimental results to theoretical concepts. In respect to technology, we discuss different specification and implementation alternatives, to show the case where the adoption of a family of standards would positively contribute to a larger acceptance and utilization of remote laboratories, and also to a wider collaboration in their development.